Solvent extraction of oleoresins from vanilla plant (vanilla planifolia andrews) bu using soxhlet extractor - Mohd Amirul Hafiza, Che Adul Aziz (2006)
In this study, Soxhlet Extraction method is one of the extraction technique can be used to extract a soluble fraction from solid medium into an organic solvent such n-hexane and ethanol. In this research, the soxhlet extraction method used to extract the vanilla plant (Vanilla planifolia Andrews) and the product is oleoresin of vanilla. To make sure a good quality of oleoresin, parameters that affect the performance of the soxhlet extraction method were investigated. The examined parameters were vanilla surface area and the solvent ratio. The yield of vanillin was observed. Ground vanilla produced higher yield compared to cut vanilla. In addition, ethanol was found to be better than hexane. Both extraction using ethanol and hexane consisted vanilla component such as vanillin.